2020
DOI: 10.3390/en13184838
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage between Economic Growth, Renewable Energy, Tourism, CO2 Emissions, and International Trade: The Evidence for the European Union

Abstract: This paper evaluates the link between economic growth, renewable energy, tourism arrivals, trade openness, and carbon dioxide emissions in the European Union (EU-28). As an econometric strategy, the research uses panel data. In the first step, we apply the unit root test, and the results demonstrated that the variables used in this study are integrated I (1) in the first difference. In the second step, we apply the Pedroni cointegration test, and Kao Residual cointegration test, and we observe that the variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(78 citation statements)
references
References 60 publications
13
65
0
Order By: Relevance
“…In this case, we observe improvements in environmental quality and pollution. According to the recent literature of Balsalobre-Lorente et al (2021), Pata and Caglar (2021), Leitão and Lorente (2020), Ike et al (2020), and Koengkan et al (2020), in the short run, there is a positive impact of income per capita on CO 2 emissions (GDP > 0); however, we expect a negative effect of income per capita (GDP < 0) on carbon dioxide emissions in the long run.…”
Section: Methodology and Datamentioning
confidence: 64%
See 4 more Smart Citations
“…In this case, we observe improvements in environmental quality and pollution. According to the recent literature of Balsalobre-Lorente et al (2021), Pata and Caglar (2021), Leitão and Lorente (2020), Ike et al (2020), and Koengkan et al (2020), in the short run, there is a positive impact of income per capita on CO 2 emissions (GDP > 0); however, we expect a negative effect of income per capita (GDP < 0) on carbon dioxide emissions in the long run.…”
Section: Methodology and Datamentioning
confidence: 64%
“…The authors defend that trade liberalization is based on trade agreements and environmental rules to decrease greenhouse gas emissions. The previous studies of Leitão and Lorente (2020), Zhang et al (2019), Roy (2017), and Leitão and Balogh (2020) found a negative correlation between trade intensity and carbon dioxide emissions (TRADE < 0); according to the literature, trade intensity promotes sustainability development.…”
Section: Methodology and Datamentioning
confidence: 86%
See 3 more Smart Citations